Living Supramolecular Polymerization of an Aza‐BODIPY Dye Controlled by a Hydrogen‐Bond‐Accepting Triazole Unit Introduced by Click Chemistry. (11th February 2020) - Wang, Houchen; Zhang, Yongjie; Chen, Yuanfang; Pan, Hongfei; Ren, Xiangkui; Chen, Zhijian
Abstract: An aza‐BODIPY dye 1 bearing two hydrophobic fan‐shaped tridodecyloxybenzamide pendants through 1, 2, 3‐triazole linkages was synthesized by a click reaction and characterized. 1 H NMR studies indicated that dye 1 exhibited variable conformations through intramolecular H‐bonding interaction, which is beneficial for the polymorphism of aggregation. The thermodynamic, structural, and kinetic aspect of the supramolecular polymerization of dye 1 was investigated by UV/Vis absorption spectroscopy, IR spectroscopy, AFM, TEM, and SEM. Biphasic aggregation pathways of dye 1, leads to the formation of off‐pathway, metastable Agg. I and thermodynamically stable Agg. II with distinct H‐aggregation spectra and nanoscale morphology. The living manner of the supramolecular polymerization of dye 1 was demonstrated in seeded polymerization experiments with temperature‐modulated successive cooling–heating cycles. Abstract : Zum Leben erweckt : Eine lebende supramolekulare Polymerisation wurde durch aza‐BODIPY 1, das als Wasserstoffbrückenakzeptor fungierende Triazoleinheiten trägt, demonstriert. Der H‐Brückenbaustein des amidverknüpften Triazols in 1 kann als Motiv zur Kodierung von Konformationsinformationen und zur Entwicklung polymorpher supramolekularer Systeme verwendet werden.